In need of a patch UP: Recurrent congenital diaphragmatic hernia presenting with a large pleural effusion - Farhana Shariff; Catherine M. McDougall; Mark A. Chilvers; Sonia A. Butterworth (Elsevier, 2014)
We report a case of recurrent congenital diaphragmatic hernia (CDH) presenting with a large unilateral pleural effusion. A 12-year old boy who had a left sided CDH repaired in the neonatal period, presented with fever, lethargy, and non-productive cough. Chest radiograph demonstrated a loculated pleural effusion. Computed tomography scan revealed recurrent herniation of abdominal contents. To our knowledge, this is the first reported case of a recurrent congenital diaphragmatic hernia presenting with large pleural effusion.